Heart, you bully, you punk - Cohen, Leah Hager (New York : Viking, 2003)
When thirty-one-year-old I.J. Esker volunteers to home-tutor Ann James after an injury, she reluctantly begins falling in love with Ann's father, Wally, which sets off a chain of events that will alter all three of their lives.
Keywords: Teenage girls -- Fiction; Teacher-student relationships -- Fiction; Domestic fiction